ANALISIS PERHITUNGAN PPh PASAL 21 DAN PPh PASAL 23 CV. INDIO MARGA EGASARANA SURABAYA - Dinda Aditya Devi; Soesilawati Soema Atmadja (Ekomania, 2023)
Taxes are an important aspect or contribution to complement and cover weaknesses in carrying out development or existing needs in government. One of income taxes is PPh Article 21 and PPh Article 23. The object of research in this study in CV. Indio Marga Egasarana, which is located in Surabaya and engaged in contracting business. This research is a qualitative research in which secondary data collection is not obtained through statistical procedures. By using sample calculation of PPh Article 21 and Article 23 PPh on CV. Indio Marga Egasarana Surabaya. Calculation and deduction systems for two companies have been carried out well. Although not done with a more professional person and company also reports its taxes on time.